If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15-(3x+1)=(x+1)+3x
We move all terms to the left:
15-(3x+1)-((x+1)+3x)=0
We get rid of parentheses
-3x-((x+1)+3x)-1+15=0
We calculate terms in parentheses: -((x+1)+3x), so:We add all the numbers together, and all the variables
(x+1)+3x
We add all the numbers together, and all the variables
3x+(x+1)
We get rid of parentheses
3x+x+1
We add all the numbers together, and all the variables
4x+1
Back to the equation:
-(4x+1)
-3x-(4x+1)+14=0
We get rid of parentheses
-3x-4x-1+14=0
We add all the numbers together, and all the variables
-7x+13=0
We move all terms containing x to the left, all other terms to the right
-7x=-13
x=-13/-7
x=1+6/7
| 20+5a=20 | | -3x-(x+4)=3 | | x/8+6=14 | | (X-5)y=3300 | | 5a+20=20 | | 7x+12+6x=1 | | 561=2x | | 5y(86-y)0=86+4y | | 5x−1=30 | | -6+49r^2=43 | | 9/15=4x | | 1/100=d^2 | | 24x+12x+6x=90 | | (5x-8)(x-5)=0 | | -5(k+1)-2(3+k)=-4 | | 5y(86-y)=86+4y4 | | 15/9=4x | | (x+1)(x+3)^2=2 | | 9+m=16 | | X=-25+1.5x | | -1=-7(p+4)+4(1-4p) | | 28x^2-4x=0 | | 4-3b=2(3b+1) | | 2u-12=8(u+3) | | 37=d-14 | | 18y/3-7=7y | | ((x^2)-(3x)-(10))/(x+4)=0 | | 18y/3-7=7 | | -50=-6(5n+5)+2(7-2n) | | x+44+55=90 | | 1/4(16x+60)=6x-5 | | x6+3x3+2=0 |